Uniform Illumination of Concentrated Sunlight in Photovoltaic Solar Modules With Plane-Focusing Fresnel Lenses - Minglei Fu; Eugene Antonov; Volodumyr Lysenko; Viacheslav Petrov; Vladimir Zenin (IEEE Photonics Journal)
An algorithm has been developed for modeling the parameters of microprismatic specialized plane-focusing Fresnel lenses. Such lenses are more effective for application in photovoltaic modules compare to the traditional point-focusing Fresnel lenses for concentrating the sunlight. The method for manufacturing above lenses by diamond cutting technique and subsequent thermal pressing of silicone blanks is proposed. The optical characteristics of new plane-focusing lenses for photovoltaic solar modules, which are made using our simulation results, have been experimentally investigated with collimated laser beam.